PETA DIGITAL DUSUN SENTONO - Jamalul Lail (Asian Journal of Innovation and Entrepreneurship, 2015)
Mapping is needing to help village’s government in order to make decisions which related to the location. Digital Mapping is choosen because the maps would be easy toto be revised and could reach  every changes fastly. Digital maps is created using GoogleEarth, and the file is delivered to the local goverment to be used as well.